Adsorption Phenomenon of Arundinaria alpina Stem-Based Activated Carbon for the Removal of Lead from Aqueous Solution. (16th June 2021) - Asrat, Yosef; Adugna, Amare Tiruneh; Kamaraj, M.; Beyan, Surafel Mustefa
Abstract : In this study, activated carbon was prepared from locally available bamboo ( Arundinaria alpina ) in Ethiopia to remove Pb (II) from wastewater. Various effects such as solution pH, initial Pb (II) ion concentration, and adsorbent dose were investigated and accordingly discussed, and the process was carried out on a batch adsorption base. Dried Arundinaria alpina stem was activated with potassium hydroxide (KOH) at a ratio of 1 : 1 (w/v) and carbonized in a furnace at three temperature ranges (500 o C, 600 o C, and 700 o C) for 3 h. The physicochemical of Arundinaria alpina stem activated carbon (AASAC) was investigated and the resultant of 500 o C treatment setup is found as ideal in terms of yield (40.6 g), ash (3.5%), porosity (0.704%), moisture (7.7%), and iodine number (814.69 mg/g). The further characterization of ideal AASAC was carried out by scanning electron microscopy (SEM), X-ray diffraction (XRD) spectroscopy, and Fourier transform infra-red (FTIR). The optimum Pb (II) removal efficiency of AASAC was 99.8% at pH 5 in a synthetic solution, but the efficiency declined to 60.42% on real industrial wastewater due to the presence of its mixed pollutant nature. Freundlich isotherm model is more favorable than Langmuir with a high correlation coefficient ( R 2 -0.9496) for Pb (II) adsorption. The study revealed that AASAC has a potential adsorption efficiency to remove the Pb (II) ion from the aqueous solution which is also recommended as an adsorbent for real industry wastewater treatment.